KARAKTERISTIK KIMIA DAN UJI ORGANOLEPTIK BERAS (STUDI KASUS DI KECAMATAN BENUA KAYONG KABUPATEN KETAPANG) - Selvianti, Isye; Nopriyanti, Marisa; Azhari, Aas (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2022)
The purpose of this research is to find out the chemical characteristics of the rice moisture contents as well as consumer's acceptance of Agro rice, Siam rice, and coriander rice in Benua Kayong district, Ketapang regency. The method used in this research is the usage of the Grain Moisture Tester device, which serves as a tool for measuring moisture content, and also aid in analysis of organoleptic scoring tests on color observation parameters done by 25 untrained panelists. According to the analysis results of the moisture contents, the rice that scored the lowest in terms of moisture content is coriander rice sold in Mr. Zain's shop (11,1%), and the highest is Pulen Kampung rice sold in Mrs. Noliya's shop (15,4%). Meanwhile, the results of the organoleptic scoring test on the parameters for observing the color of rice, the best result was found in Agro rice sold in Ari's shop with the score of 7,92 (bright white), and the rice with the lowest score is Sumpit rice sold in Nando's shop with the score of 5,68 (light gray).